Hubungan Dukungan Keluarga Dan Tingkat Stres Terhadap Kadar Gula Darah Penderita Diabetes Melitus Di Puskesmas Kecamatan Koja - Nur Aulia Fikri (2021)
Diabetes mellitus is a chronic disease characterized by insufficient pancreatic beta cells to produce insulin or when the body cannot use insulin effectively. To prevent an increase in DM and high blood sugar levels, regularity in diabetes control is needed, and in this control, of course, family support and good stress levels are needed so that sufferers feel comfortable, confident and enthusiastic in carrying out these controls so that blood sugar levels will increase. always under control. The purpose of this study was to determine the relationship between family support and stress levels on blood sugar levels of people with Diabetes Mellitus at the Koja District Health Center. The method used in this study is descriptive analytic with a cross-sectional approach using non-probability sampling with accidental sampling technique with a total sample of 138 samples. Univariate analysis in this study used a frequency distribution and bivariate analysis used the Chi-Square test. The results showed that there was a relationship between family support and blood sugar levels in DM patients with a (p-value 0.000) and a relationship between stress levels and blood sugar levels in DM patients with a (p-value 0.000). The results of this study are expected to be a source of information for people with diabetes so that they are always regular in controlling diabetes by always involving their families in self-care and the elderly with diabetes must manage stress well.